Current Experimental Studies of Gene Therapy in Parkinson's Disease - Lin, Jing-ya; Xie, Cheng-long; Zhang, Su-fang; Yuan, Weien; Liu, Zhen-Guo (Frontiers in Aging Neuroscience, 2017)
Parkinson’s disease (PD) was characterized by late-onset, progressive dopamine neuron loss and movement disorders. The progresses of Parkinson’s disease affected the neural function and integrity. To date, most researches had largely addressed the dopamine replacement therapies, but the appearance of L-dopa-induced dyskinesia hampered the use of the drug. And the mechanism of PD is so complicated that it’s hard to solve the problem by just add drugs. Researchers began to focus on the genetic underpinnings of Parkinson’s disease, searching for new method that may affect the neurodegeneration processes in it. In this paper, we reviewed current delivery methods used in gene therapies for PD, we also summarized the primary target of the gene therapy in the treatment of PD, such like neurotrophic factor（for regeneration）, the synthesis of neurotransmitter（for prolong the duration of L-dopa）, and the potential proteins that might be a target to modulate via gene therapy. Finally, we discussed RNA interference therapies used in Parkinson’s disease, it might act as a new class of drug. We mainly focus on the efficiency and tooling features of different gene therapies in the treatment of PD.